Toolkits for smarter cities - Degbelo, Auriol (2018)
Degbelo, A., Bhattacharya, D., Granell, C., & Trilles, S. (2016). Toolkits for smarter cities: a brief assessment. In C. R. García, P. Caballero-Gil, M. Burmester, & A. Quesada-Arencibia (Eds.), Ubiquitous Computing and Ambient Intelligence (pp. 431-436). ( Lecture Notes in Computer Science). Springer International Publishing.